2021
DOI: 10.1111/rda.13913
|View full text |Cite
|
Sign up to set email alerts
|

The effects of luteinizing hormone as a suppression factor for apoptosis in bovine luteal cells in vitro

Abstract: The fate of the corpus luteum, a transient endocrine gland formed and degraded during an oestrous cycle, is decided by various physiological factors, such as luteinizing hormone (LH). As a stimulator of progesterone, LH is known to maintain corpus luteum functional and structural integrity by inhibiting apoptosis, a programmed cell death. Therefore, we aim to investigate its action during the mid‐luteal phase hypothesized that LH suppresses the death mechanism of bovine luteal steroidogenic cells (LSC) by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…We also found that the number of follicles increased in the diestrus stage after BCR feeding; this was associated with high levels of FSH in the proestrus, producing more follicles [40]. The CL is a temporary endocrine gland formed during ovulation [41]. The addition of PRL inhibited hCG-induced ovulation in a dose-related fashion [42].…”
Section: Effect Of Prl On Follicle Count and CL Numbermentioning
confidence: 99%
“…We also found that the number of follicles increased in the diestrus stage after BCR feeding; this was associated with high levels of FSH in the proestrus, producing more follicles [40]. The CL is a temporary endocrine gland formed during ovulation [41]. The addition of PRL inhibited hCG-induced ovulation in a dose-related fashion [42].…”
Section: Effect Of Prl On Follicle Count and CL Numbermentioning
confidence: 99%
“…LH or CG treatment promotes the viability of luteinized granulosa or luteal cells in vitro [ 231 , 262 264 ] and protects the CL from regression in vivo [ 265 267 ]. The molecular changes that link LHCGR activation to anti-apoptotic effects include upregulation of BCL-2 [ 262 , 267 , 268 ], MCL-1 [ 263 ], survivin [ 269 ], and anti-oxidant enzymes [ 264 ] with simultaneous suppression of BAX and CD95/Fas/Apo-1 [ 262 , 268 ]. The exact mechanisms facilitating these LH/CG effects in the luteal cells are still undetermined, but they may be mediated through PKA-CREB regulation of gene expression [ 258 ].…”
Section: Regulation Of Pcd During Luteolysismentioning
confidence: 99%
“…Increased concentrations of ANGPT1 can lead to reduced inflammation, apoptosis, and fibrosis within tissues [40,41]. Reduction in inflammation and apoptosis is important for reproductive tissues since apoptosis results in a reduction in cell proliferation, follicular atresia, and CL regression [42]. Another important role of ANGPT1 is stabilizing vasculature within cells and tissues [41].…”
Section: Lipid and Cytokine Profiles During Early To Mid-luteal Phasementioning
confidence: 99%